Post-partum depression: Its association with IYCF practices and effect on child growth indicators in urban slums of Mumbai, India - Sharyu Mhamane; Yashoda Karande; Vanisree Ramanathan (Elsevier, 2024)
Background: The nexus of postpartum depression (PPD) does not limit itself to maternal health but has a profound impact on child health through compromised caregiving and nursing practices of the mother. This impairs child's cognitive, emotional, and physical health during crucial stages of growth. Objective: The paper aims to identify the association between PPD and Infant and Young Child Feeding practices and the effect of PPD on child growth during the first 1000 days of life in urban slum settings of Mumbai. Results: For infants below six months of age, bottle-feeding practices, initiation of breastfeeding within 1 hour of birth, and exclusive breastfeeding for the first 2 days were associated with PPD (p < 0.05). For children, 6-24 months, minimum meal frequency, minimum dietary diversity, zero consumption of fruits and green vegetables, and initiation of semisolid and soft food were associated with the postpartum depression status of the mother (p < 0.05). The infants of the depressed mothers were 10 %, 16 % and 20 % more likely to be underweight, wasted and stunted as compared to infants of the mothers who do not show symptoms of PPD. Conclusion: Measurement of prevalence of PPD is essential to manage it. It is essential to build mental health inclusive policies/programmes for mother and child health, engage in capacity building of grassroot workers to spread awareness about PPD, and be skilled to identify and refer the early signs of PPD.